Comparing two theories about the nature of soil phosphate. (20th August 2020) - Barrow, N. J.
Abstract: Two theories about the nature of phosphate in soil are current. One holds that soil phosphate is mostly present as particles of iron, aluminium and calcium phosphates: the precipitate‐particulate theory . The other holds that phosphate is mostly adsorbed and penetrates heterogeneous, variable‐charge particles: the adsorption‐penetration theory . This is the only theory that is consistent with and can be deduced from observations. It is my contention that the persistence of the precipitate‐particulate theory leads to: wasted research effort in trying to identify the supposed phosphate fractions; failure to recognize the long‐term changes in soil phosphate due to repeated applications, and thus to over‐fertilisation; and misapprehension about the effects of pH on phosphate availability.